THE IMPACT OF FEMALE DIRECTORS ON FIRM PERFORMANCE: EVIDENCE FROM INDONESIA - Triana .; Marwan Asri (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
This research shows the impact of female directors on firm performance in Indonesia by using as its sample the public companies listed on the Indonesian Stock Exchange (IDX) from 2011 until 2015. There were 347 companies, with 1,735 samples observed. This research uses the multiple regression method. The model is a modified model from 9 recent articles published between 2012 and 2015. The empirical result shows that a female director has a positive significant effect on firm performance. The control variables, consisting of leverage, firm size and firm age have negative significance for firm performance. This research is conducted across 9 sectors of industrial classification, which support the International Finance Corporation (IFC) in increasing the number of female directors in Indonesia. For managers, this research will promote gender development in the boardroom, female executive training programmes as well as female representation on boards of directors. For regulators, this research may provide a contribution to gender representation in board’s policies, rules and regulations. This research can build awareness of women’s contributions to firms and encourage a greater female presence in the boardroom.